The Effect of Social Media Marketing on Brand Awareness to Purchase Intention on Apartment Products - Syafitri, Elza; Syahil, Moh. Choiru; Pancoro W., Rudi Wahyu; Srihadi, Tara Farina (Journal of Management Economic and Financial, 2025)
This study examines the influence of social media marketing on brand awareness and purchase intention for apartment products. In the digital marketing era, platforms such as Facebook, Instagram, and Twitter are key in reaching and interacting with target audiences. This study aims to identify and determine how the influence of content creation involvement and attributes of social media marketing (SMM) activities in order to influence brand awareness and subsequently increase purchase intention in purchasing apartment products, Corporate Credibility and Brand Self Congruity variables are also added in order to identify the influence on purchase intention. The research method used is using the PLS-SEM calculation method. The research findings show that social media marketing activities, especially the factors of Interaction, Entertainment, Customization, Trendiness and Electronic Word-of-Mouth have a significant effect on brand awareness, among these factors the most influential on Brand Awareness is Electronic Word-of-Mouth. In addition, Brand Awareness, Corporate Credibility and Brand Self-Congruity are proven to have a significant positive relationship with Purchase Intention, but among these variables that have a significant influence is Brand Self-Congruity. This research was conducted in urban areas in Jakarta, Bogor, Depok, Tangerang and Bekasi, which requires further research to cover other major cities in Indonesia and consider additional variables that influence the overall purchasing decision process specifically for Apartment products. Insights from this research are useful for marketers or developers or entrepreneurs interested in the property sector, especially in formulating digital marketing strategies and the use of social media marketing to increase brand visibility and purchase motivation.